2007
DOI: 10.1080/13803390600629775
|View full text |Cite
|
Sign up to set email alerts
|

Verbal learning and memory deficits in Mild Cognitive Impairment

Abstract: Criteria for amnestic MCI rely on the use of delayed recall tasks to establish the presence of memory impairment. This study applied the California Verbal Learning Test to detail memory performance in MCI patients (n = 70), as compared to control subjects (n = 92) and AD patients (n = 21). Learning across the 5 trials was different among the 3 groups. Learning strategy was also different, the MCI group showing less semantic clustering than the control group. However, both MCI patients and controls could benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 44 publications
(47 reference statements)
13
89
1
Order By: Relevance
“…However, correctly encoded items appear to remain preserved in memory since AD patients are able to correctly recall and recognize these items with the help of semantic cues (Oltra-Cucarella, Pérez-Elvira, & Duque, 2014). Conversely, MCI patients benefit from semantic cueing, but only when cognitive support is provided (cued recall), although they show less semantic clustering than healthy adults (Ribeiro, Guerreiro, & De Mendonça, 2007).…”
mentioning
confidence: 99%
“…However, correctly encoded items appear to remain preserved in memory since AD patients are able to correctly recall and recognize these items with the help of semantic cues (Oltra-Cucarella, Pérez-Elvira, & Duque, 2014). Conversely, MCI patients benefit from semantic cueing, but only when cognitive support is provided (cued recall), although they show less semantic clustering than healthy adults (Ribeiro, Guerreiro, & De Mendonça, 2007).…”
mentioning
confidence: 99%
“…Few published studies have investigated strategy use in MCI patients, and the available data are conflicting. Studies have suggested that MCI patients have difficulty using semantic clustering spontaneously (Ribeiro et al, 2007;Malek-Ahmadi et al, 2011;Hutchens et al, 2012). Another study (Bennett et al, 2006) suggested that MCI patients use similar memory strategies as normal controls but continue to present lower performance.…”
Section: Discussionmentioning
confidence: 99%
“…Malek-Ahmadi, Raj, & Small (2011) and Ribeiro, Guerreiro, & De Mendonça (2007) suggested that MCI patients tend to use less semantic clustering spontaneously during word list recall tasks. However, results from the latter study indicated that older adults with MCI benefited from using semantic cues.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, however, MCI patients have been shown to have poorer performance than controls on tasks of semantic memory, receive less bene fi t than controls when semantically cued on memory tasks, and use less semantic clustering strategies on verbal learning tasks [ 67,99,100 ] . It may be the case that these de fi cits in semantically related learning are due at least in part to dampened executive functioning processes that affect categorization or semantic organization [ 101 ] .…”
Section: Common Neurocognitive De Fi Citsmentioning
confidence: 97%